FINANCIAL PERFORMANCE ANALYSIS AS A BASED FOR FORMULATING A STRATEGIC PLAN FOR BUSINESS UNIT DEVELOPMENT - Steven Siaila; Dientje Rumerung (Universitas Padjadjaran, 2022)
A study of all aspects of management needs the attention of the management. Financial Management with Financial Performance Analysis summarises the results of the implementation of various company policies in a certain period. It should be an essential management element. This study aimed to examine the determination of business strategies in the context of developing business units based on the results of financial performance analysis. The analysis period in this writing was the period 2012-2019. The analytical technique used in this research was descriptive quantitative that utilized several financial ratios to formulate business unit development strategies that referred to the Five Forces of Michael Porter and SWOT analysis. Based on the calculation result of several financial ratio analyzes, it can be concluded that the financial performance of PD Pantja Karya experienced good results at the beginning of the analysis period, namely 2012 to 2015 or 2016. In the period after 2014-1017, PD Pantja Karya’s financial performance tends to be bad. Using the Five Forces of Michael Porter analysis and SWOT analysis, it can be concluded that PD Pantja Karya continued the timber business unit to be carried out by implementing a stability strategy supported by several business management policies. Shipping and land transportation business units should implement a Development Strategy by focusing on operational efficiency.